Genetic variability studies for yield and yield attributes in Indian mustard (Brassica juncea L.): GENETIC VARIABILITY STUDIES FOR YIELD AND YIELD ATTRIBUTES IN INDIAN MUSTARD - VINAYAKUMAR ARAGI; B P MARUTHI PRASAD; B R PATIL (Journal of Oilseeds Research, 2023)
Mustard (Brassica juncea L.) cultivation was largely confined to northern India, although climate change paved the way for crop introduction to southern parts of the country. This fall, an investigation was conducted to evaluate 68 Indian mustard genotypes in the Main Agricultural Research Station, Dharwad (University of Agricultural Sciences, Dharwad) in rabi 2018-19. The objective of the present study is to study the genetic variability for yield and yield attributes in Indian mustard. The results of genetic variability study indicated that significant genotypic variation in key traits such as secondary branches, racemes per plant, economic yield, biological yield, harvest index, seed yield, seeds per siliqua, siliqua length, number of siliqua per raceme, and oil yield. Traits like days to 50% flowering, days to maturity, and oil content exhibited low variation. Additionally, traits with high heritability, including plant height, primary branches, racemes per plant, and several yield-related parameters, showed substantial genetic advance,suggesting the potential for effective selection and rapid improvement in these characteristics.